"Either go through chemotherapy or go through dying": A qualitative study of the experiences of treatment decision-making among older newly-diagnosed adults with acute myeloid leukemia. Issue 28 (1st October 2022) - Mhina, Carl J; Teal, Randall; Cole, Amy C.; Adapa, Karthik; Bryant, Ashley Leak; Wood, William Allen; Richardson, Daniel R.
Abstract : 253 Background: Treatment decision making for older adults with acute myeloid leukemia (AML) is complex. An informed discussion between the patient and physician that incorporates patient values and preferences is crucial to arrive at a personalized treatment plan. We sought to understand the patient experience of treatment decision making and identify challenges to aligning care to patient preferences. Methods: We conducted in-depth interviews with newly diagnosed older (≥60 years) adults with AML and their caregivers following a semi-structured interview guide. Qualitative thematic analysis was used to summarize findings. Results: 16 in-depth interviews were conducted. Major themes emerged including: 1) Patients were overwhelmed and in shock ("I was shocked." "... like my face was hit with a water hose turned all the way up." "It's like you have been hit by a truck.") 2) Patients felt powerless, without true treatment options ("You don't feel like you are in the driver seat." "I didn't see that there was a decision to be made." "I mean, I had no choice." "Either go through chemotherapy or go through dying.") 3) Patients felt rushed and unprepared to make a treatment decision ("I don't feel like we were prepared at all. It was all thrown in your face, and you had to decide." "But the mindset when they went through the typical course of chemo... laying that all on me in a two-hour period and wanting me to decide right there and then, I think that that should not be allowed... you can't make sound decisions in a two-hour period about your life and whether you are going to live or not.") 4) Patients predominantly followed physician recommendations for treatment ("What went through my mind was I was told that I had a great doctor who was going to be looking at me and I leave stuff like that up to the professionals." "They told me what needed to be done and I just let them do it.") 5) Patients balanced many factors when making treatment decisions including survival, quality of life, and spending time with family ("Dr. [Name], I want to live long and strong." "And both of us prefer quality for a shorter time than we do a longer time in agony." "I'm not scared to die... it's just the fact that I'll miss everyone.") 6) Patients desired greater input on care plans ("[I suggest] trying to let the patients have a little bit of input on their treatment plan." "It has to be catered to the patients making those decisions."). Conclusions: Older adults with newly diagnosed AML feel overwhelmed, unprepared, and rushed into treatment decisions. No one factor dominated treatment decision making highlighting the need for physicians to assess individual patient priorities to arrive at a treatment plan. Interventions to reduce distress, elicit patient preferences and values, and increase participation in treatment decision making would improve the quality of treatment decisions.